Macro-level comparison of the banking system in Ukraine and Poland - Girchenko, Tetiana Dmytrivna; Serdiukova, Olha Ivanivna; Gongalo, Natalia (Poznań University of Technology Publishing House, 2020)
The article analyzes the features of the banking systems in Ukraine and Poland. The main factors influencing the dynamics of the banking sector in Ukraine are systematized. A retrospective analysis of the banking system’s formation shows that during this period it experienced 4 crises, the catalysts of which are both external and internal factors. The mecha-nism of functioning of the National Bank of Ukraine’s (NBU) banking supervision system is considered in detail, in particular, the mechanism of control over the functioning of the coun-try's banking system, identification of risks in the activities of banking institutions (CAMELSO rating, determination of early response indicators, etc.). The main achievements of the Ukraine’s banking system in 2019 in terms of seven strategic goals are considered, and the directions for future work are outlined. In order to follow the positive useful experience of Poland, the main stages of the country’s banking system formation are analyzed. Much attention is paid to the aspect of consolidation of bank capital from Polish owners. Due to these actions, it was possible to achieve a significant increase in the volume of banking services in the country and the growth of the banking system as a whole. There is also a significant disparity in the amount of the minimum authorized capital in the banks of Poland and Ukraine and it is proposed that they should reduce the minimum amount of authorized capital for the banks of Ukraine.
Keywords: banks; authorized capital; regulator; banking system; threats; factors; reforming